2015
DOI: 10.3892/ol.2015.3563
|View full text |Cite
|
Sign up to set email alerts
|

Application of eupatilin in the treatment of osteosarcoma

Abstract: Abstract. 5,7-dihydroxy-3' ,4' ,6-trimethoxyflavone, commonly known as eupatilin, is a traditional Asian medicinal plant, which is mainly used for the treatment of gastritis, as well as its use as an anti-inflammatory agent. Eupatilin is a bioactive compound; however, its effects on osteosarcoma (OS) have remained to be elucidated. Therefore, the present study aimed to investigate the effects of eupatilin on this malignant bone tumor, using the U-2 OS cell line. The experimental results revealed that eupatilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous study had revealed the anti‐proliferation and apoptosis induction mechanisms of eupatilin involved in mitochondrial intrinsic pathway of osteosarcoma cells . Similarly, herein, we explored the functions of eupatilin in regard to proliferation inhibition, cell cycle arrest, and apoptosis induction in cervical cancer.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous study had revealed the anti‐proliferation and apoptosis induction mechanisms of eupatilin involved in mitochondrial intrinsic pathway of osteosarcoma cells . Similarly, herein, we explored the functions of eupatilin in regard to proliferation inhibition, cell cycle arrest, and apoptosis induction in cervical cancer.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, eupatilin has shown anti‐diabetic, anti‐arthritis, and anti‐proliferative activity. Importantly, eupatilin's anti‐cancer properties have been found in multiple cancers, including human oesophageal cancer, renal cancer, glioma, osteosarcoma, and gastric cancer . However, no literature has explored the role of eupatilin in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Eupatilin has an inhibitory effect on a variety of tumors. Eupatilin induces apoptosis of osteosarcoma U-2OS cells through mitochondrial endogenous pathways and inhibits the proliferation of osteosarcoma cells [18]. Eupatilin has a significant therapeutic effect on gastric cancer, and it inhibits the growth of gastric cancer cells by blocking STAT3-mediated vascular endothelial growth factor expression [19].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis indicated that it was able to cause the mitochondrial apoptotic pathway, by the enhanced Bax/Bcl-2 ratio, decrease in mitochondrial membrane capability, the release of cytochrome c, caspase-3 and -9 activation and PAPR cleavage detected in the U2-OS cells. Hence, eupatilin may, therefore, represent a novel anticancer drug for use in the treatment of OS [33].…”
Section: 7dihydroxy3'4'6trimethoxymentioning
confidence: 99%